1994
DOI: 10.1021/ma00083a012
|View full text |Cite
|
Sign up to set email alerts
|

Light-Scattering and TEM Analyses of Virtual Upper Critical Solution Temperature Behavior in PCL/SAN Blends

Abstract: It has been known that blends of poly(6-caprolactone) (PCL) and poly(styrene-ron-acrylonitrile) (SAN) show a miscibility window and, at the edges, lower critical solution temperature (LCST) behavior occurs. The presence of a virtual upper critical solution temperature (UCST) of PCL/SAN blends was found at lower temperatures as follows. Time-resolved light scattering under Vv and Hv optical alignments was used in order to distinguish two competitive processes-crystallization and liquid-liquid phase separation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…The D app for phase dissolution was found to have values between 3 and 11 Â 10 À17 m 2 s À1 over the temperature range of 50 to 115 C. Closer to LCST, the values decrease; they are also low in the range of 50-65 C. The diffusion should be slower at a lower temperature due to a lower mobility. In the present case, the presence of a virtual UCST of about 40 C, as was found earlier for similar systems [29], should cause the decrease in D app . Comparable values of D app for phase separation (but of opposite sign, i.e., negative values) were found in the temperature range of 125 to 150 C. By further increasing the temperature the SD would proceed much more quickly, an example being value of D app at 180 C which was more than 10-fold higher than the fastest phase dissolution.…”
Section: Time-resolved Light Scattering 173supporting
confidence: 83%
See 1 more Smart Citation
“…The D app for phase dissolution was found to have values between 3 and 11 Â 10 À17 m 2 s À1 over the temperature range of 50 to 115 C. Closer to LCST, the values decrease; they are also low in the range of 50-65 C. The diffusion should be slower at a lower temperature due to a lower mobility. In the present case, the presence of a virtual UCST of about 40 C, as was found earlier for similar systems [29], should cause the decrease in D app . Comparable values of D app for phase separation (but of opposite sign, i.e., negative values) were found in the temperature range of 125 to 150 C. By further increasing the temperature the SD would proceed much more quickly, an example being value of D app at 180 C which was more than 10-fold higher than the fastest phase dissolution.…”
Section: Time-resolved Light Scattering 173supporting
confidence: 83%
“…It is reasonable that the curve has a minimum because, according to thermodynamic calculations, the miscibility window might be a "closed" area under some circumstances [34]. An experimentally obtained LCST border and a calculated miscibility loop are also shown in Figure 5.46 [29].…”
Section: Determination Of Virtual Ucst Behavior 199mentioning
confidence: 94%
“…[14] Numerous studies have been carried out to modify PCL by blending or co-polymerization with other polymers. [15][16][17][18][19][20][21][22][23][24][25] In the case of PCL/SAN blend, the miscibility of this system and the influence of acrylonitrile (AN) content in the copolymer upon blend miscibility have been studied by Chiu et al [20] They found that SAN and PCL are miscible when the AN content in SAN ranges from 8 to 28 wt.-%. Savoboda et al [21,22] studied the morphology of PCL/SAN blend via competition with spinodal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ether sulfone) is a chemically inert and highly thermostable polymer showing a hydrophobic surface which leads to high fibrinogen adsorption and subsequent thromboembolization [111]. This effect is generally avoided by non-desirable heparin doses.…”
Section: Inactivation Of Polymer Surfacesmentioning
confidence: 99%